What makes a giant fruit? Assembling a genomic toolkit underlying various fruit traits of the mammoth group of Cucurbita maxima - Reddy, Umesh K.; Natarajan, Purushothaman; Abburi, Venkata Lakshmi; Tomason, Yan; Levi, Amnon; Nimmakayala, Padma (Frontiers in Genetics, 2022)
Since their introduction during the early 16th century in Europe, pumpkins (Cucurbita maxima Duch.) have rapidly dispersed across the world mainly because of their suitability to become integrated with the local cuisine, high nutritive value and long shelf life, and wide adaptation across geographical regions of the world. Competition for growing the showy type or mammoth-sized pumpkins that produce the largest fruit of the entire plant kingdom has drawn attention and passion among the scientific community and general public. In this study, we used genome-wide single nucleotide polymorphisms to resolve admixture among the pumpkin groups and resolved the population differentiation, genome-wide divergence and evolutionary forces underlying the formation of mammoth-sized pumpkin. Our admixture analysis clearly showed that the mammoth group (also called Display or Giant) primarily evolved from the hubbard group with an introgression from the buttercup group, thus indicating fusion of two horticulture groups. We inferred a genetic toolkit and archived a set of private alleles underlying known fruit developmental genes, selective sweeps, and shared and novel haplotypes involved in the evolutionary mechanisms. Our genome-wide association study identified three major allelic effects underlying various fruit-size genes in this study. For fruit weight, a missense variant in the homeobox-leucine zipper protein ATHB-20-like (S04_18528409) was strongly associated (false discovery rate = 0.000004) with fruit weight, and the higher allelic effect was consistent across the 3 years of the study. A cofactor (S08_217549) on chromosome 8 was found in strong association with fruit length, showing a superior allelic effect across the 3 years. A missense variant (S10_4639871) on translocation protein SEC62 was a cofactor for fruit diameter. Several known molecular mechanisms were found involved in the determination of giant fruit size, including endoreduplication, hormonal regulation, CLV-WUS signaling pathway, MADS-box family, and ubiquitin-proteasome pathway. This study provides a general framework for the molecular evolutionary relationship among the horticulture groups of C. maxima and provides insight into the evolutionary origins of rare variants contributing to the giant fruit size and associated changes.